(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A new Eriosomatine aphid (Zelkovaphis trinacriae gen. n., sp. n.) living on Zelkova sicula in Sicily is described. To the same genus are tentatively referred the W-Asiatic Schizoneura caucasica Dzhibladze, living on Z. carpinifolia in Caucasus, and the E-Asiatic Hemipodaphis persimilis Akimoto, living on Z. serrata in Japan; a key is given to separate al ate emigrants of the three aphid species. A taxonomical and morphological account is given of the new genus, focussing on its relationships with other Eriosomatinae genera. Adult morphs of Z. trinacriae on primary host and first instar nymphs of fundatrix and exules are described, and notes are added on its open, leaf-roll gall and biological behaviour. The aphid secondary host plant is hitherto unknown.